Landasan Filosofis Keterampilan Komunikasi Konseling - Hariko, Rezki (Jurnal Kajian Bimbingan dan Konseling, 2017)
Counseling is a professional activity involving the relationship between a counselor with an individual or a group of individuals. Like an interpersonal relationship in general, in the process of counseling occurs the process of interaction and communication between individuals with other individuals (counselors-counselee). Mastery of communication skills is a basic prerequisite for counselors to be able to use various counseling skills effectively and efficiently. It should be understood that almost all of the counseling skills involve the counselor’s communication skills. A good understanding of communication skills should be based on an in-depth study and understanding of communication philosophy. Mastery of communication skills will facilitate the counselor in using various counseling skills that have been formulated by experts as assets to provide successful assistance services for the counselee.